HASIL PEMANTAPAN MUTU INTERNAL PEMERIKSAAN HbA1c - Doni Setiawan Doni Setiawan (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2020)
HbA1c is a small component of hemoglobin that binds to blood sugar. Quality Control is usually done by examining the control material that has known the range value and comparing the results of the inspection tool with the range of the control material. HPLC (High Performance Liquid Chromatography) is an analytical chemical technique used to separate components in a mixture. The purpose of this study was to determine the Internal Quality Stabilization on HbA1c examination using Hb Analyzer. The method used is descriptive. The technique of collecting data uses primary data. Data is obtained by conducting control material checks during the control period which is carried out for 26 days and the data is processed computerically then plotted into the graph. Based on research in May-June 2019 good results were obtained, where not deviant